Casas elevadas a orillas del rio - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se pudo observar casas construidas con tipo elevacion del suelo al piso principal alas orillas del rio por la crecida del rio.
ENGLISH: houses built with a type of elevation of the ground to the main floor could be observed on the banks of the river due to the flooding of the river.

SPANISH: Se pudo observar casas construidas con tipo elevacion del suelo al piso principal alas orillas del rio por la crecida del rio.
ENGLISH: houses built with a type of elevation of the ground to the main floor could be observed on the banks of the river due to the flooding of the river.
Elevated houses on the banks of the river
Keywords: Iquitos (Perú)|~|Houses--Peru|~|Rural Infrastructure--Housing--Peru|~|Houses|~|Iquitos (Perú)|~|Casas|~|Perú|~|Estructura Rural|~|Viviendas|~|Perú|~|Casas|~|Iquitos (Perú)|~|Houses|~|Peru|~|Rural Infrastructure|~|Housing|~|Peru|~|Houses